Accident Information System using Open Source and IoT - Prahlatha Varadhan T. P. M, Ganeshkumar S, Mohanraj K, Bhaskar K (Journal of Information & Systems Management, 2020)
In the rising world of human population, the demand on the manufacturing sector particularly the automobile sectors are given with a high pressure to improve safety on their automotive systems. As there in rise in population there is also a high risk on increase n number of accidents occurring on roads, a survey says that around every accident are occurring every minute across the country. The accident does only end with the damage of vehicle but also pushes the passengers to a fatal and emergency situation. This project uses open source to communicate the position and details of the owner of the car to the nearby hospitals, police stations, service stations and one neighbor. This AMS uses open source using raspberry pie, crash sensor, GPS module and cameras that uses IoT and have the facility of live recording in them. Thus, it communicates to the nearby hospital and police control hub thereby reducing the time delay for the medical treatment and the formality for further police enquiry.